Learning and teaching strategies for the history of Bolivian education among young university students in Educational Sciences (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
The teaching and learning of the history of education in university education over the last decade has been problematized by the need to transcend the teaching of historical content—dates, data, concepts, figures, and educational policies—toward fostering the historical skills of the historicized individual. Specifically, this article describes and explains the experience of learning and teaching the history of Bolivian education with young university students in the Educational Sciences program at the Salesian University of Bolivia, in terms of the use of innovative strategies and techniques for developing theoretical and practical classes. Based on the history of education, students, on the one hand, demonstrate their perceptions of the techniques implemented; on the other, they develop a historical-cultural vision of educational events from a critical position on social and educational reality based on knowledge, action, coexistence, and historical being.
Keywords: higher education; youth; history of education; education students; innovative techniques